Analisis Moving Average Convergence Divergence dan Relative Strength Index pada Perdagangan Saham di IDX-MES BUMN 17 : Analysis of Moving Average Convergence Divergence and Relative Strength Index in Stock Trading on IDX-MES BUMN 17 - Mega Tunjung Hapsari (Islamic Economic Management & Entrepreneurship, 2026)
This research is motivated by the rapid development of the capital market, particularly in stock trading activities. Technological advances have made it easier for various groups to access the capital market and conduct stock transactions more efficiently. In response to this situation, the researcher took the initiative to provide education on applying technical analysis to achieve optimal profits. The research focuses on three technical analysis indicators: the Moving Average Convergence Divergence (MACD), the Relative Strength Index (RSI), and the Stochastic Oscillator, using the IDX-MES BUMN 17 index as the object. The research aims to test each indicator's effectiveness—MACD, RSI, and Stochastic Oscillator—in generating capital gains from stock trading. The research method used is quantitative, with a sample of buy and sell signals taken from the IDX-MES BUMN 17 index. The researcher collected secondary data using TradingView software and analysed it through a difference test using SPSS 25 software. The analysis revealed two main findings: the MACD indicator is ineffective in generating capital gains, and the RSI indicator only partially affects capital gains.